"Fish Gill" Incisions for Severe Periorbital Surgical Emphysema Following Tension Pneumothorax – A Case Report and Review of the Literature. (December 2021) - Patel, Manal Irshad Ahmed; Barabas, Anthony
ABSTRACT: Background: Surgical emphysema refers to the presence of air within the subcutaneous space and is a known complication of chest drain insertion. Symptoms range from mild crepitus of the chest wall to the accumulation of air in the face and neck, which can ultimately result in cardiovascular compromise. Objective: The aim of this article is to present a rare case of cervical, facial and periorbital surgical emphysema following chest drain insertion, and describes a novel use of 'fish gill' incisions in the palpebromalar groove with an associated review of the literature. Case Report: A 68-year-old gentleman presented with acute dyspnoea due to a right-sided tension pneumothorax. Emergency decompression with a Seldinger chest drain resulted in persistent cervical, facial and periorbital surgical emphysema causing difficulty in movement, inability to open the eyes and progressive risk to cervical venous return. "Fish gill' incisions at the lateral-most edge of the palpebromalar groove, down to the level of the orbicularis oculi muscle, rapidly released air from the face and neck, alleviating discomfort, reducing venous compression and restoring vision. Conclusion: Cervical, fascial and periorbital surgical emphysema may be resolved with the use of "fish gill" incisions at the lateral palpebromalar groove and simple drains. To the best of our knowledge, this method has not been reported previously in the literature.